2019
DOI: 10.1111/jocd.13008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of high‐intensity focused ultrasound in facial and neck rejuvenation

Abstract: Background: High-intensity focused ultrasound (HIFU) has recently been introduced in the treatment of facial wrinkles and laxity. Objective:The purpose of the study was to evaluate efficacy and safety of HIFU in facial and neck rejuvenation.Methods: High-intensity focused ultrasound treatment was performed on face and neck by using two different probes with focal depth of 3 mm and 4.5 mm. Two independent, blinded clinicians evaluated the clinical improvement at 3 months after treatment. The patients also score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
0
19
0
1
Order By: Relevance
“…Both studies on the facial region evaluated patient satisfaction. 24,26 Shome et al 24 used a subjective assessment scale at 6 months and Aşiran Serdar et al 26 performed assessment at 3 months after treatment for each area. The patients scored their satisfaction on a scale of 1 to 4, ranging from not satisfied to very satisfied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies on the facial region evaluated patient satisfaction. 24,26 Shome et al 24 used a subjective assessment scale at 6 months and Aşiran Serdar et al 26 performed assessment at 3 months after treatment for each area. The patients scored their satisfaction on a scale of 1 to 4, ranging from not satisfied to very satisfied.…”
Section: Resultsmentioning
confidence: 99%
“…Transient erythema and numbness in the mandibular region were reported as adverse events that were temporary and resolved spontaneously within 10 days. 26…”
Section: Discussionmentioning
confidence: 99%
“…Several inflammatory proteins activate keratinocytes and activated keratinocytes express VEGF, which is important for angiogenesis. [ 19 ] Furthermore, the targeting of angiogenesis is known to be a successful therapeutic strategy for rosacea. [ 21 ] Therefore, we performed cell migration, tube formation and cell proliferation assays on mouse endothelial cells (SVEC4‐10) exposed to different RF conditions, namely, 8 watt (W) to 12 W for 80‐120 ms Best results were obtained at 10 W, 100 ms, and thus, these conditions were used for the assays (Figures ).…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have suggested that RF irradiation be viewed as an alternative treatment option, but all have cited clinical experiences without experimental data. [ 18,19,37 ] Empirically, we found that radiofrequency irradiation in clinical trials conducted on rosacea patients could improve rosacea lesions similar to those with IPL or pulsed dye lasers and the radiofrequency irradiation reduces heating sensation, which is the most uncomfortable symptom among the various symptoms that rosacea patients complain. The present study provides experimental results and evidence that supports the use of RF for the treatment of rosacea (Figure 4 and Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation